ANALISIS BIAYA DAN MUTU PENGGUNAAN STEEL FIBER PADA RIGID PAVEMENT DENGAN METODE EKSPERIMENTAL LABORATORIUM (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2021)
Indonesia as a developing country is still using concrete in its construction. By modifying one or more component on the concrete construction, it will affect the cost saving and the quality of the construction. The current innovation in concrete technology in developed country is the mixture of steel fiber in the concrete construction. This study aims to find and compare the cost and quality of the use of steel fiber (dramix) and iron wiremesh in the rigid pavement. The method used in this study is a laboratory experiment. The study results that steel fiber costs less and is more economic than reinforcing steel in rigid pavement. In 1m3 concrete with reinforcing iron wiremesh m8 costs Rp. 2.138.343,26. However, a concrete in mixture of 10% steel fiber (dramix) costs Rp. 1.798.089,00. There is cost savings Rp. 340.254,26 in 1m3. The mixing of steel fiber in concrete has 28 days longer compressive strength than the ordinary concrete mix with compressive strength value fc’ 29,07Mpa. However, concretes with the mix of 15%: fc’ 29,38Mpa, 20%: fc’ 29,41MPa, and 30%: fc’ 29,58Mpa. In flexural strength test, the concrete with iron wiremesh m8 results flexural strength fc’ 4,978MPa. However, a concrete with the mix of steel fiber (dramix) has more flexural strength that differs within level; 10%: fc’ 5,173Mpa, 15%: fc’ 5,316Mpa, 20%: fc’ 5,458Mpa, and 30%: fc’ 5,707Mpa. steel fiber (dramix) has more compressive strength that varies in level; 10%: fc’ 29,34MPa